An overview on fast pyrolysis of the main constituents in lignocellulosic biomass to valued-added chemicals: Structures, pathways and interactions. (November 2015) - Shen, Dekui; Jin, Wei; Hu, Jun; Xiao, Rui; Luo, Kaihong
Abstract: Considering the huge demand of energy for social economic development and deterioration of environment due to extensive utilization of fossil fuels, green and renewable energy sources are standing in the centre for alleviating the mentioned pressure and diversifying the global energy supply. "Pyrolysis", as one of the promising thermo-chemical conversion technologies, could convert biomass to value-added chemicals and fuels in forms of solid, liquid and gas. Fast pyrolysis of the main constituents in biomass (polysaccharides and lignin averagely accounting for 90 wt%), involving the yield of liquid/solid/gas products, distribution of prominent oxygenate compounds, their formation pathways associated with the chemical structure of highly polymerized macromolecules, would be vigorously discussed in this review work, helping to improve the understanding of pyrolytic behavior of biomass, optimize the thermal conversion process and so on. Meanwhile, the interaction among the components during pyrolytic process was evidenced and briefly overviewed, in order to shorten the distance between the pyrolysis of biomass and pyrolytic behavior of its main components and design the new-concept co-pyrolysis process for promoting the production of oxygenated compounds. The challenges and wayforward in the field are addressed in estimating the formation priority of specific oxygenate compounds and developing new technology for producing the value-added compounds (chemicals) in high yields.